An empirical study of ransomware attacks on organizations: an assessment of severity and salient factors affecting vulnerability. Issue 1 (28th December 2020) - Yuryna Connolly, Lena; Wall, David S; Lang, Michael; Oddson, Bruce
Abstract: This study looks at the experiences of organizations that have fallen victim to ransomware attacks. Using quantitative and qualitative data of 55 ransomware cases drawn from 50 organizations in the UK and North America, we assessed the severity of the crypto-ransomware attacks experienced and looked at various factors to test if they had an influence on the degree of severity. An organization's size was found to have no effect on the degree of severity of the attack, but the sector was found to be relevant, with private sector organizations feeling the pain much more severely than those in the public sector. Moreover, an organization's security posture influences the degree of severity of a ransomware attack. We did not find that the attack target (i.e. human or machine) or the crypto-ransomware propagation class had any significant bearing on the severity of the outcome, but attacks that were purposefully directed at specific victims wreaked more damage than opportunistic ones.